2019
DOI: 10.1103/physrevphyseducres.15.020121
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing relevance in physics education: Using a systems view to expand our conception of making physics relevant

Abstract: A common hope of many physics educators and researchers is that students leave the course with a stronger sense that physics is relevant to them than when they entered the course. Multiple survey measures have attempted to measure shifts in students' beliefs on the relevance of physics but frequently the results show a negative shift in students' beliefs and are often reported as a failure of students to "see the relevance." We challenge this interpretation by first operationalizing relevance as a construct by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Here, drawing on Bernstein (1999), Airey and Larsson (2018) have discussed how physics knowledge needs to be both repackaged and recontextualized by physics teachers for use by students in school and society. Last, there is the question of relevance, which has been thoroughly connected to student motivation and results in the literature (Afjar et al, 2020;Bennett et al, 2016;Gaffney, 2013;Nair & Sawtelle, 2019). For trainee physics teachers to be motivated to learn physics, it has been shown that clear connections between the physics content and a teacher future is significant (Gaffney, 2013).…”
Section: The Content Assumptionmentioning
confidence: 99%
“…Here, drawing on Bernstein (1999), Airey and Larsson (2018) have discussed how physics knowledge needs to be both repackaged and recontextualized by physics teachers for use by students in school and society. Last, there is the question of relevance, which has been thoroughly connected to student motivation and results in the literature (Afjar et al, 2020;Bennett et al, 2016;Gaffney, 2013;Nair & Sawtelle, 2019). For trainee physics teachers to be motivated to learn physics, it has been shown that clear connections between the physics content and a teacher future is significant (Gaffney, 2013).…”
Section: The Content Assumptionmentioning
confidence: 99%
“…The general alignment of our results with IPLS research in spite of the broader interdisciplinary population of this course suggests that future research concerning this course should, like this project, adapt the processes of IPLS research to the Pomona context. For example, our data strongly suggest that authentic interdisciplinary gestures (examples, applications, and connections) serve as sources of engagement and interest, but as Geller et al [6] and Nair and Sawtelle [27] remind us, engagement, interest, and relevance are complex constructs with varied meanings. Not only would adapting such IPLS research to the General Physics context provide useful information to support research-based reformation of this course, but also, given the centrality of physics-biology as their interdisciplinary context, it is worth investigating how the results of Refs.…”
Section: Discussionmentioning
confidence: 60%
“…Not only would adapting such IPLS research to the General Physics context provide useful information to support research-based reformation of this course, but also, given the centrality of physics-biology as their interdisciplinary context, it is worth investigating how the results of Refs. [6,27] as well as Refs. [11,28,29] transfer and compare to different interdisciplinary contexts.…”
Section: Discussionmentioning
confidence: 85%
“…Perceived relevance has recently become a focus within PER literature. More recent efforts include a focus on perceived relevance within well-known attitudinal surveys in physics [25] or in terms of pre-service physics teachers' issues with their own perceived relevance of physics to their teaching careers. [26] In particular, it is a concern that life science majors, e.g.…”
Section: B Theoretical Framework For Implementationmentioning
confidence: 99%